2021
DOI: 10.3390/ijgi10050290
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution Characteristics of Heavy Metals in Surface Soil of Xilinguole Coal Mining Area Based on Semivariogram

Abstract: Heavy metal pollution is a major environmental problem facing humankind. Locating the source and distribution of heavy metal pollutants around mines can provide a scientific basis for environmental control. The structure effect and random effect of a semivariogram can be used to determine the reason for spatial differences in the heavy metal content in surface soil, and the coefficient of variation and regression analysis can be used to confirm that the verification accuracy meets the geostatistical requiremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…Meanwhile, the proportion of serious degradation in the subsidence center was 5.64% by trend analysis method, which was twice and five times that in the subsidence edge and non-subsidence zones. It can be found that the coefficient of variation and trend analysis methods have the same development trend in the mining areas, and combining the two methods to monitor the surface vegetation can better analyze the vegetation characteristics [8,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the proportion of serious degradation in the subsidence center was 5.64% by trend analysis method, which was twice and five times that in the subsidence edge and non-subsidence zones. It can be found that the coefficient of variation and trend analysis methods have the same development trend in the mining areas, and combining the two methods to monitor the surface vegetation can better analyze the vegetation characteristics [8,21].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that Landsat NDVI can effectively monitor the temporal and spatial variation characteristics of surface vegetation in seven open-pit coal mines, such as Pingshuo, Curragh, Appalachian, Keshutang, Jiazibei, Yimin, and Shengli. Meanwhile, the spatial variability of soil and vegetation characteristics can be expressed by the coefficient of variation [2,[17][18][19][20][21]; therefore, it can be known from the above literature survey that most of the studies mainly analyzed the surface vegetation of opencast coal mines, less attention has been placed on the surface vegetation degradation caused by underground coal mining, and synchronous monitoring of regional surface subsidence and vegetation degeneration researches are relatively limited [3,22]. In particular, there are few studies on coal mining and its effect on surface vegetation in Xishan Coalfield of Shanxi Province.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated semi-variance function values can be fitted by a series of theoretical models and characterized by nugget variance (C0), Sill (C0+C) and range, which represent the measurement error or spatial variation, the maximum variance between data pairs and the farthest distance of correlation between graphic parameters, respectively. The nugget to sill (N:S ) ratio [C0/(C0+C)] of ≤0.25 means strong spatial dependency, which indicate the variation of heavy metals mainly affected by the structural effect of the natural environment; the ratio remains between 0.25 and 0.75 which means moderate spatial dependency, indicating the variation of heavy metals mainly affected by the joint action of the natural environment factors and the random factors of human activities; and the ratio of ≥0.75 suggests weak spatial dependency, which indicates the variation of heavy metals mainly affected by human activities [ 20 , 21 ]. Main natural factors include climate, parent material, topography and soil properties, and human activities including fertilization, farming measures and cropping systems.…”
Section: Methodsmentioning
confidence: 99%
“…Geostatistics and geographic information system (GIS) techniques have been widely employed to quantify the spatial distribution of soil properties to reduce uncertainties, minimising costs and to identify pollution sources, especially in areas of mined soil (Chen et al, 2021;Kulikova et al, 2019). It has additional advantages in research as its analysis includes the characteristics of space and time changes.…”
Section: Introductionmentioning
confidence: 99%